Coastal Erosion Variability at the Southern Laptev Sea Linked to Winter Sea Ice and the Arctic Oscillation - Nielsen, David Marcolino; Dobrynin, Mikhail; Baehr, Johanna; Razumov, Sergey; Grigoriev, Mikhail (Geophysical Research Letters, 2020)
Arctic coastal erosion experiences pronounced effects from ongoing climate change. The Laptev Sea figures among the Arctic regions with the most severe erosion rates. Here, we use unprecedentedly long records of almost 30 years of annual in-situ coastal erosion rate measurements from Bykovsky Peninsula and Muostakh Island to separate the main modes of variability, which we attribute to large-scale drivers. The first (lower-frequency) and second (higher-frequency) modes are associated with winter sea-ice cover in the Laptev Sea and with the Arctic Oscillation, respectively, which together account for 85.1±24.1% of the total observed variance. Arctic coastal erosion has so far been neglected in Earth system models (ESMs). The proposed mechanisms set favorable conditions for coastal erosion at large scales (synoptic to planetary scales), compatible with those represented in modern ESMs.